Petrographic and geochemical characterization of the early formative stages of Northern Adriatic shelf rocky buildups. (March 2018) - Franchi, Fulvio; Bergamasco, Andrea; Da Lio, Cristina; Donnici, Sandra; Mazzoli, Claudio; Montagna, Paolo; Taviani, Marco; Tosi, Luigi; Zecchin, Massimo
Abstract: A peculiar type of marine rocky outcrops is generated under temperate conditions through the cementation of carbonate and siliciclastic sediments on the northwestern Adriatic shelf. The lithification process results into the genesis of punctiform outcrops ( tegnùe ) that serve as substrate to substantial coralligenous epibenthic growth. These buildups have been often described as beachrock. More recently, an alternative genetic mechanism, implying precipitation of carbonate cements in the marine phreatic zone, has been hypothesized for the rocky outcrops off the coast of Chioggia (south of Venice). These rocky outcrops are settled along the levee of meandering channels inherited from Pleistocene fluvial systems. Petrographic analyses of the Chioggia rocky outcrops allowed distinguishing three (3) main lithofacies: 1) biofouled sandstone blocks; 2) cross-stratified slabs and 3) bioclastic carbonates. These lithofacies have a common substrate mainly made by allochemic sandstone and sandy allochem limestone consisting in rounded grains of limestones and dolostones. The host sediments are cemented by a thin micrite coating followed by isopachous rims of scalenohedral and bladed calcite. Geochemical analyses revealed a sensible decrease in Mg contents between the early and late generations of isopachous cements. Vadose cements are missing suggesting that the precipitation of calcite cements occurred in marine phreatic zone without supra-tidal exposure. The lack of aragonite cements suggests that seawater was mixing with meteoric groundwater. The mixing of groundwater induced a partial dissolution of high-Mg calcite and precipitation of a later stage low-Mg calcite. The lithification of the morphologies inherited from Pleistocene fluvial systems provided the nucleus for the development of the coralligenous buildups observed in the North Adriatic Sea shelf. It is possible that diagenetic processes, other than those normally responsible for the formation of beachrocks worldwide, have been active in the northern Adriatic Sea starting from the post-Last Glacial Maximum transgression. It is therefore likely that these processes are more relevant for the coralligenous epibenthic growth in temperate siliciclastic shelves than previously thought. Highlights: We study petrography and geochemistry of shallow marine concretions in the Adriatic. These concretions are settled on Pleistocene meandering fluvial morphologies. Lack of vadose cements suggests precipitation of calcite within marine phreatic zone. The mixing of groundwater during diagenesis induced a partial dissolution of calcite. The concretions provide the nucleus for the development of coralligenous buildups.